PENGATURAN HUKUM TENTANG PENGAWASAN WILAYAH DIRGANTARA INDONESIA TERHADAP LALU LINTAS PESAWAT UDARA ASING DITINJAU DARI PERSPEKTIF HUKUM INTERNASIONAL - Muhammad Denny Yusril Siregar; Abdul Rahman; Sutiarnoto Sutiarnoto (Journal of USU International Law, 2017)
ABSTRACT LEGAL SETTLEMENT ON THE SUPERVISION OF AREA REGIONAL AREA TO TRAFFIC AIRCRAFT AIRCRAFT IS REVIEWED FROM INTERNATIONAL LEGAL PERSPECTIVEThe issue of air traffic control and security and the safeguarding of aircraft is an important apek in legal arrangements made by countries. One aspect that needs to be taken into consideration in the utilization of air space and its resources is the jurisdiction problem. The problem of the regulation of Indonesian state air law. International air law arrangements. The legal arrangements on the supervision of Indonesia's aerospace territory against foreign air traffic are reviewed from the perspective of international law. Type of research or approach method that is done is normative law research method.The nature of the research is descriptive analytical. Research using descriptive analystis. The legal arrangement of Indonesian state airspace, namely Article 4 and Article 5 of Law no. 1 of 2009 concerning Aviation, aviation activities constitute a form of activity and or effort on the territory of sovereignty over the airspace authorized and liable to the Government as stipulated in Article 5 of Law no. 1 In 2009, that in the framework of the implementation of the sovereignty of the state over the territory of the Republic of Indonesia the Government shall exercise the authority and responsibility of the regulation of air space for the interests of defense and security of the state, aviation and national economy. Arrangement of international airspace law, namely Article 38 (1) of the Statute of the International Court of Justice, namely the legal sources of International Law, in the article which became the source of International Law, namely: Paris Convention 1919, Chicago Convention 1944 International Practices, Recognized by the civilized nation and Jurisprudence. The legal arrangements on the supervision of Indonesia's aerospace territory against foreign air traffic are reviewed from the perspective of international law, namely Law no. 1 of 2009 on Aviation, Law no. 24 of 1992 on Spatial Planning, Law no. 43 of 2008 on State Territory, Law Number 37 Year 2002 concerning the rights and obligations of foreign ships and aircraft in exercising the archipelagic sea lanes right and Government Regulation no. 3 of 2001 on the Security and Safety of Aviation, Government Regulation no. 70 of 2001 on the Airport. Keywords: Legal Arrangement, Supervision of Indonesia Aerospace Area Foreign Air Traffic